The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/ofid/ofy210.824
|View full text |Cite
|
Sign up to set email alerts
|

987. Repeated Exposure to an Adjuvanted Quadrivalent Subunit Influenza Virus Vaccine (aQIV): A Randomized, Observer Blind, Multicenter Study

Abstract: BackgroundThe safety, immunogenicity, and efficacy associated with administration of of aQIV in children 6 months through 5 years of age was investigated.1 Although enhanced immunogenicity in children was demonstrated for MF59-adjuvanted influenza vaccines after first administration, the impact of repeated vaccination on immunogenicity and safety has not been evaluated.MethodsA total of 607 subjects who participated in parent study, now aged 12 months through 6 years, were enrolled the subsequent year and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In pediatric population, recent studies showed that the high-dose IV was more immunogenic than the standard one in children with leukemia or solid tumors and in solid organ transplant patients but not in children with HIV (84), with good reported safety profile (8486). Given the relatively small studied population, despite the evidences that immunocompromised children generate a lower immune response to standard-dose IV compared to healthy subjects (87), no definitive recommendation about the use of the high-dose IV can be drawn. Notably, no data about the use of this high dose IV are available in immunocompromised children, and younger than 2 years.…”
Section: Ongoing Discussion and Future Perspectivesmentioning
confidence: 99%
“…In pediatric population, recent studies showed that the high-dose IV was more immunogenic than the standard one in children with leukemia or solid tumors and in solid organ transplant patients but not in children with HIV (84), with good reported safety profile (8486). Given the relatively small studied population, despite the evidences that immunocompromised children generate a lower immune response to standard-dose IV compared to healthy subjects (87), no definitive recommendation about the use of the high-dose IV can be drawn. Notably, no data about the use of this high dose IV are available in immunocompromised children, and younger than 2 years.…”
Section: Ongoing Discussion and Future Perspectivesmentioning
confidence: 99%